2006
DOI: 10.1126/science.1120925
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Cdx2 Gene Expression and Trophectoderm Lineage Specification in Mouse Embryos

Abstract: Controversy exists as to whether individual blastomeres from two-cell-stage mouse embryos have identical developmental properties and fate. We show that the transcription factor Cdx2 is expressed in the nuclei of cells derived from the late-dividing but not the first-dividing blastomere of two-cell embryos and, by lineage tracing and RNA interference knock-down experiments, that this lagging cell is the precursor of trophectoderm. Cdx2 mRNA is localized toward the vegetal pole of oocytes, reorients after ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
3
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 25 publications
2
56
3
1
Order By: Relevance
“…Recently, it has been suggested that localized maternal Cdx2 mRNA and protein can be detected before the eight-cell stage and that maternal Cdx2 is involved in TE formation (Deb et al, 2006). However, knockdown experiments using RNA interference strategies have led to conflicting results, with one group finding preblastocyst lethality (Deb et al, 2006) and another finding phenocopy of zygotic null Cdx2 mutants (Meissner and Jaenisch, 2006).…”
Section: Maintenance Of the Icm/te Lineage Restrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been suggested that localized maternal Cdx2 mRNA and protein can be detected before the eight-cell stage and that maternal Cdx2 is involved in TE formation (Deb et al, 2006). However, knockdown experiments using RNA interference strategies have led to conflicting results, with one group finding preblastocyst lethality (Deb et al, 2006) and another finding phenocopy of zygotic null Cdx2 mutants (Meissner and Jaenisch, 2006).…”
Section: Maintenance Of the Icm/te Lineage Restrictionmentioning
confidence: 99%
“…However, knockdown experiments using RNA interference strategies have led to conflicting results, with one group finding preblastocyst lethality (Deb et al, 2006) and another finding phenocopy of zygotic null Cdx2 mutants (Meissner and Jaenisch, 2006). Ultimate proof of the functional role of maternal Cdx2 will be provided by analysis of germline null mutants.…”
Section: Maintenance Of the Icm/te Lineage Restrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the lack of the TE lineage generates a "biological artifact" (Hurlbut, 2005), because it creates a disorganized clump of cells. Detailed studies from the laboratories of Rossant and Beck provided excellent insight into the role of Cdx2 (Chawengsaksophak et al, 1997(Chawengsaksophak et al, , 2004Strumpf et al, 2005), the earliest known TE-specific transcription factor (Strumpf et al, 2005;Deb et al, 2006).…”
Section: Technological Solution To Ethical Objections: Altered Nucleamentioning
confidence: 99%
“…In mice, whether a blastomere is to become a trophoblast or an ICM cell appears to be specifi ed by its position during the fi rst cleavage (Piotrowska et al 2001 ) . It was also demonstrated that asymmetrical distribution of the Cdx2 gene product in mouse oocytes and embryos defi nes the lineage of the trophectoderm (Deb et al 2006 ) . In correlation with studies in which a signal for ICM or trophectoderm lineage is present in some blastomeres far earlier than when the phenotypical characteristics emerge, the earliest signs of cellular differentiation occur during the compaction stage in human embryos (Piotrowska et al 2001 ;Edwards 2005 ;Hansis et al 2004 ) .…”
Section: Human Embryonic Stem Cells From Laboratory and Clinical Pmentioning
confidence: 99%